Diseño, construcción y análisis funcional-experimental de una cocina solar combinada (PARVATI - TIPO CAJA) para el laboratorio de energías renovables de la CIEM-UNL. - Uyaguari Carrión, César Oswaldo (2014)
This research work is based on a comparative analysis of two types of kitchens construction easy and low cost, as are kitchen box and double angle (Parvati), from which the best features and benefits extracted functional, with the purpose of obtaining a new model or type of cuisine that combines the qualities of the prototypes compared. The new prototype and its features make up a new source of efficient use of solar energy, without neglecting two of the main advantages of its predecessors that are low cost and easy preparation.